2017
DOI: 10.1111/obr.12638
|View full text |Cite
|
Sign up to set email alerts
|

Decreased 5‐HT2cR and GHSR1a interaction in antipsychotic drug‐induced obesity

Abstract: Second generation antipsychotics (SGAs), notably atypical antipsychotics including olanzapine, clozapine and risperidone, can cause weight gain and obesity side effects. Antagonism of serotonin 2c receptors (5-HT2cR) and activation of ghrelin receptor type 1a (GHSR1a) signalling have been identified as a main cause of SGA induced obesity. Here we review the pivotal regulatory role of the 5-HT2cR in ghrelin-mediated appetite signalling. The 5-HT2cR dimerizes with GHSR1a to inhibit orexigenic signalling, while 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 91 publications
1
11
0
Order By: Relevance
“…To the best of our knowledge, the present study is the first to report that 95% of 5‐HT2c receptors overlapped with NPY‐GFP neurons in the Arc. Risperidone is a potent 5‐HT2c receptor antagonist, and previous studies have demonstrated that obesogenic antipsychotic drugs reduce 5‐HT2c receptor inhibition of GSHR1a . Therefore, our results indicate that risperidone may selectively stimulate NPY expression in the Arc by reducing 5‐HT2c receptor activity, thereby increasing food intake.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…To the best of our knowledge, the present study is the first to report that 95% of 5‐HT2c receptors overlapped with NPY‐GFP neurons in the Arc. Risperidone is a potent 5‐HT2c receptor antagonist, and previous studies have demonstrated that obesogenic antipsychotic drugs reduce 5‐HT2c receptor inhibition of GSHR1a . Therefore, our results indicate that risperidone may selectively stimulate NPY expression in the Arc by reducing 5‐HT2c receptor activity, thereby increasing food intake.…”
Section: Discussionsupporting
confidence: 63%
“…In contrast to their non‐obesogenic counterparts, obesogenic SGAs are commonly associated with potent 5‐HT2c receptor antagonism . A previous study reported that 5‐HT2c receptors can inhibit the expression of orexigenic growth hormone secretagogue receptor 1a (GHSR1a) in the hypothalamus .…”
Section: Introductionmentioning
confidence: 99%
“…5‐HT2C receptors can increase inositol triphosphate (IP3) and diacylglycerol, open calcium channels, and release calcium stores, which promote neurite growth . 5‐HT2C receptors have nonedited and edited forms . The edited isoform of 5‐HT2C receptor has a suppressive effect on neurite growth, which could be reversed by a 5‐HT2C receptor inverse agonist .…”
Section: Antipsychotic Drug‐targeted Receptors Regulate Neurites In Smentioning
confidence: 99%
“…Interestingly, some researchers have suggested that weight gain and other metabolic effects may be linked to the improvement of symptoms ( 3 ). These side effects are most likely related to the high affinity of these compounds for other receptor systems in the brain, which are involved in regulation of appetite and food intake ( 4 6 ). Such effects can have a deleterious impact on the overall health of patients and can potentially lead to conditions such as insulin resistance, type 2 diabetes, obesity, and cardiovascular complications ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%